METHOD OF REANALYSIS AFTER RECONSTITUTION OF THE DYNAMIC FLEXIBILITY MATRIX FOR A MODIFIED DISSIPATIVE SYSTEM - et. al., Omar Dadah; Hammou Ait Rimouch, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In structural dynamics, several problems are solved with the help of formulations using matrices of frequency response functions. This article focuses on the exploitation and evaluation of these matrices. A technique of structural modifications, based on knowledge of the introduced modifications as well as the frequency response functions relating to the original structure, will first be described. Then, we will be interested in the evaluation of the used flexibility matrices. These can be either calculated from a mathematical model, or derived from experimental observations. In practice, only a limited number of the dynamic flexibility matrix columns can be measured. A technique to complete this matrix is proposed, following the description of the conventional techniques. The idea is combined with a procedure which makes it possible to choose, for the numerical tests, an optimal placement of the excitations. The proposed formulation is based on the use of clean solutions and is validated by a digital example.